2021
DOI: 10.3390/ijerph18041850
|View full text |Cite
|
Sign up to set email alerts
|

Association between Mental Health Knowledge Level and Depressive Symptoms among Chinese College Students

Abstract: This study aimed to explore the association between mental health knowledge level and the prevalence of depressive symptoms among Chinese college students. A cross-sectional study was conducted in six universities in Jinan, Shandong Province, China, and a total of 600 college students were recruited to self-complete a series of questionnaires. The Mental Health Knowledge Questionnaire (MHKQ) was used to investigate the level of mental health knowledge. Depressive symptoms were investigated with the depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Females are more likely to internalize their negative feelings, whereas males resort to externalizing behaviors such as smoking and alcoholism[ 42 - 44 ]. However, some analyses did not find significant sex differences[ 28 , 45 , 46 ]. Other studies have shown that men have a higher prevalence of depression[ 20 , 47 ].…”
Section: Nonpathological Influencing Factors Of Depressionmentioning
confidence: 99%
“…Females are more likely to internalize their negative feelings, whereas males resort to externalizing behaviors such as smoking and alcoholism[ 42 - 44 ]. However, some analyses did not find significant sex differences[ 28 , 45 , 46 ]. Other studies have shown that men have a higher prevalence of depression[ 20 , 47 ].…”
Section: Nonpathological Influencing Factors Of Depressionmentioning
confidence: 99%
“…A study reported that the number of patients with mental disorders increased by 67% from 2015 to 2019, and 70% of internal medicine department visits were due to stress [6]. Additionally, the incidence rate of depression due to college students' stress was approximately 24% [7]. Depression can negatively affect interpersonal relationships, daily activities, and academic performance, and worsening depression can increase the frequency of high-risk behaviors such as suicide attempts.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, we found hints that psychology students, especially female students, appear to be less psychologically distressed in terms of depressive mood problems and worrying during the pandemic. A possible explanation for our ndings is provided by the results of a Chinese study of Cheng et al [22]. They found hints in their pre-pandemic data that higher mental health knowledge was associated with lower levels of depressive symptoms.…”
Section: Discussionmentioning
confidence: 70%